2020
DOI: 10.1097/md.0000000000023862
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid hemorrhage and COVID-19

Abstract: Some evidences suggest the involvement of the central nervous system in patients infected with SARS-CoV-2. We aim to analyze possible associations between coronavirus disease 2019 (COVID-19) pandemic and spontaneous subarachnoid hemorrhage (SAH), in a comprehensive neurological center. We conducted a retrospective case series of 4 patients infected by COVID-19, who developed spontaneous SAH. Clinical data were extracted from electronic medical records. Between March 24, 2020, and May 22, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 47 publications
0
38
0
2
Order By: Relevance
“…A number of IC manifestations of COVID-19 have been reported, mainly stroke, encephalitis, and encephalopathies [2,3]. Very few IC hemorrhages have been reported, most of which were found to be subarachnoid hemorrhages [4]. This case is of a young man with a fatal IVH without any obvious source of intraparenchymal hemorrhage.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A number of IC manifestations of COVID-19 have been reported, mainly stroke, encephalitis, and encephalopathies [2,3]. Very few IC hemorrhages have been reported, most of which were found to be subarachnoid hemorrhages [4]. This case is of a young man with a fatal IVH without any obvious source of intraparenchymal hemorrhage.…”
Section: Discussionmentioning
confidence: 85%
“…There has been emerging evidence of COVID-19 being associated with a myriad of intracerebral (IC) pathology such as stroke, encephalitis, and encephalopathy [2,3]. Cezar-Junior et al [4] demonstrated four rare cases of subarachnoid hemorrhage in COVID-19 patients. Intraventricular hemorrhage (IVH) commonly occurs as complication of IC or subarachnoid hemorrhages; primary IVH are a rare occurrence, accounting for about 3.1% of all IC hemorrhages [5].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 71 articles (127 patients) that satisfied the criteria mentioned above were included in this review. In this review, 80 cases of patients developed IS during COVID-19 infection (Aasfara et al 2021 ; Abdulkadir et al 2020 ; Agarwal et al 2020 ; Al-Mufti et al 2021 ; Al Saiegh et al 2020 ; Appavu et al 2021 ; Ashraf and Sajed 2020 ; Avula et al 2020 ; Bessa et al 2020 ; Bigliardi et al 2020 ; Burkert and Patil 2020 ; Co et al 2020 ; Dakay et al 2020a , b ; de Almeida Lima et al 2020 ; de Lorenzo Alvarez et al 2021 ; Deliwala et al 2020 ; Dumitrascu et al 2020 ; Efendizade et al 2020 ; El Nahas et al 2020 ; Elshereye and Erdinc 2020 ; Eskandarani et al 2021 ; Fu et al 2021 ; Garg et al, 2020 ; Gemcioglu et al 2020 ; Goette et al 2020 ; Goldberg et al 2020 ; Guillan et al 2020 ; Iqbal et al 2021 ; Kwon et al 2020 ; Mahboob et al 2020 ; Mansour et al 2020 ; Mirzaee et al 2020 ; Morassi et al 2020 ; Mowla et al 2020 ; Patel et al 2020a , b ; Patel et al 2020a , b ; Prasad et al 2021 ; Priftis et al 2020 ; Rajdev et al 2020 ; Rascón-Ramírez et al 2020 ; Roy et al 2021 ; Valderrama et al 2020 ; Viguier et al 2020 ; Zhai et al 2020 ), 32 cases developed intracranial hemorrhage (Ahmad et al 2021 ; Al-Mufti et al 2021 ; Al Saiegh et al 2020 ; Carroll and Lewis 2021 ; Cezar-Junior et al 2020 ; Dakay et al 2020a , b ; Dakay et al 2020a , ...…”
Section: Resultsmentioning
confidence: 99%
“…There are many case reports of intracerebral hemorrhage in adults with COVID 19 but reports is children are lacking. Basirjafari et al reported subarachnoid hemorrhage (SAH) as a severe neurological manifestation associated with pediatric COVID-19 in a 9-year-old child [12].…”
Section: Discussionmentioning
confidence: 99%